Perceptions of Long-Term Care Nurses and Nursing Assistants about Communication Related to Residents’ Care - Gretchen Ward; Elizabeth Rogan (Journal of Long-Term Care, 2021)
Context: Research shows ineffective healthcare team communication is linked to sentinel and adverse healthcare events (Gooch 2016; Robson 2016; Wagner et al. 2018). Long-term care (LTC) facilities face unique challenges of caring for frail elderly (Young 2003), who are at increased risk for cascading negative health events beginning with functional decline (Lakshmi 2014). Frequent, effective nursing team communication is essential to providing safe care for these individuals. (Castle 2007; Cortes et al. 2004; Foulkes 2011; Griffin et al. 2016; Howe 2013; Madden et al. 2017; Siegel & Young 2010).